Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T14:57:15+01:00
P(x)+Q(x), P(x)-Q(x) i P(x)*Q(x).

P(x)+Q(x)=-2x²-2x+8-x²-2x+2=-3x²-4x+10

P(x)-Q(x)=-2x²-2x+8-(-x²-2x+2)=-2x²-2x+8+x²+2x-2=-x²+6

P(x)*Q(x)=(-2x²-2x+8)*(-x²-2x+2)=
=2x⁴+4x³-4x²+2x³+4x²-4x-8x²-16x+16=2x⁴+6x³-8x²-20x+16
2010-02-01T15:31:23+01:00
P(x)=-2x²-2x+8
Q(x)=-x²-2x+2

P(x)+Q(x)=-2x²-2x+8+(-x²-2x+2)=-2x²-2x+8-x²-2x+2=-3x²-4x+10

P(x)-Q(x)=-2x²-2x+8-(-x²-2x+2)=-2x²-2x+8+x²+2x-2=-x²+6

P(x)*Q(x)=(-2x²-2x+8)(-x²-2x+2)=
=2x⁴+4x³-4x²+2x³+4x²-4x-8x²-16x+16=
=2x⁴+6x³-8x²-20x+16